A comparative study to compare the efficacy of hyperbaric bupivacaine alone and hyperbaric bupivacaine with clonidine in caudal block in paediatric lower abdominal surgeries - Garaniya, Roopal Rambhai; Gautam, Vaishali; Ruparel, Ritu (International Journal of Advances in Medicine, 2017)
Background: The aim was to compare the efficacy of addition of clonidine to hyperbaric bupivacaine and to compare it with plain hyperbaric bupivacaine for caudal analgesia in children aged 3 months to 3 years in term of analgesic duration, hemodynamic change and degree of sedation. Methods: Sixty ASA I and II children undergoing lower abdominal surgeries were divided into two groups of 30 each, plain hyperbaric bupivacaine group (Group B) and hyperbaric bupivacaine with clonidine group (Group C). Group B received only bupivacaine and Group C received bupivacaine with clonidine in caudal block. Results: Hemodynamic and demographic profiles were comparable between both the groups. Addition of clonidine significantly prolonged duration of caudal analgesia and significantly reduce the FLACC scores in group C as compared to group B. Mean sedation score immediately after postoperative period was higher in group C but after 4 hours of awakening, there was gradual fall in mean sedation score in both groups. Conclusions: Addition of clonidine to bupivacaine in caudal analgesia significantly increases the duration of post-operative analgesia.